2008
DOI: 10.2522/ptj.20070127
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Musculoskeletal Disorders in Physical Therapists: A Prospective Cohort Study With 1-Year Follow-up

Abstract: Work-related musculoskeletal disorders are prevalent in physical therapists. Physical therapy exposures, patient handling, and manual therapy, in particular, increase the risk for WMSDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
200
4
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(235 citation statements)
references
References 48 publications
14
200
4
17
Order By: Relevance
“…West and Gardner [7] reported that 16% of physiotherapists first experienced their injury as students, whereas 56% reported their worst injury to have occurred within the first 5 years of working as a physiotherapist. The most common region of injury is the low back [3,4,6,7]. In our study, only 17.7% of physiotherapy students had never experienced LBP.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…West and Gardner [7] reported that 16% of physiotherapists first experienced their injury as students, whereas 56% reported their worst injury to have occurred within the first 5 years of working as a physiotherapist. The most common region of injury is the low back [3,4,6,7]. In our study, only 17.7% of physiotherapy students had never experienced LBP.…”
Section: Discussionmentioning
confidence: 49%
“…To the best of our knowledge, this was the first study that clearly demonstrated the association between undergraduate physiotherapy study and LBP. There are many reports in the literature concerning the burden of work-related musculoskeletal injuries in physiotherapists [3][4][5][6][7]. West and Gardner [7] reported that 16% of physiotherapists first experienced their injury as students, whereas 56% reported their worst injury to have occurred within the first 5 years of working as a physiotherapist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations